Narrative inquiries into curriculum-making in teacher education - Kitchen, Julian; Parker, Darlene Ciuffetelli; Pushor, Debbie (Advances in research on teaching, 2011)
The authors explore how individuals identity and personal practical knowledge are being formed, shifted or interrupted through moments in teacher education which the authors have carefully and thoughtfully constructed. The particularity of the stories, expressed in this collection, provide us with multiple perspectives and multiple entry points into making deeper sense of the complexity of curriculum-making in teacher education. As the stories of experience resonate with our own or as they stand apart from them, they provoke us to re-imagine teacher education, and to retell and relive our own stories of teacher education with new possibility. Narrative inquiry offers teacher educators a way to move the telling of stories of curriculum- making in teacher education forward, to delve more deeply into stories in order to make sense of experience and to attend more closely to a curriculum of life that is educative for the self and others in teacher education.